1994
DOI: 10.1177/00220345940730100301
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic and Chemotactic Responses of Human Periodontal Ligament Cells to the Different Isoforms of Platelet-derived Growth Factor

Abstract: A major focus of studies that center on regeneration of the periodontium is to determine the efficacy of the use of polypeptide growth factors. Platelet-derived growth factor has been reported to be a possible agent for clinical use. PDGF has various isoforms. Therefore, we decided to study the mitogenic and chemotactic responses of human periodontal ligament (PDL) cells to recombinant human PDGF-AB, AA, and BB. Addition of each isoform of PDGF to in vitro mitogenesis assays induced PDL cell proliferation in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 54 publications
4
70
1
2
Order By: Relevance
“…All of these participate in the wound-healing process, but, until now, only the three isoforms PDGF-AA, BB and AB were evaluated in periodontal therapy. PDGF-BB is the most effective on PDL cell mitogenesis and matrix biosynthesis [75,76]. Several preclinical studies were performed using the combination of PDGF-BB and IGF-I for periodontal and peri-implant bone regeneration [77][78][79][80][81][82], culminating in the first study in humans using growth factors for periodontal regeneration [83].…”
Section: Growth Factor Applications For Oral and Periodontal Tissue Ementioning
confidence: 99%
“…All of these participate in the wound-healing process, but, until now, only the three isoforms PDGF-AA, BB and AB were evaluated in periodontal therapy. PDGF-BB is the most effective on PDL cell mitogenesis and matrix biosynthesis [75,76]. Several preclinical studies were performed using the combination of PDGF-BB and IGF-I for periodontal and peri-implant bone regeneration [77][78][79][80][81][82], culminating in the first study in humans using growth factors for periodontal regeneration [83].…”
Section: Growth Factor Applications For Oral and Periodontal Tissue Ementioning
confidence: 99%
“…5 The mean values and standard deviations of both cell count and cell shape were then calculated per each group. One way analysis of variance (ANOVA) using Scheffee test was used for multiple comparisons among different experimental groups, and paired t test was used to compare between the different incubation time periods within each experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the use of BB homodimer of PDGF since the cellular response of PDL fibroblasts to PDGF depend on the expression of a and b PDGF receptors, which are protein tyrosine kinase receptors as suggested by Heldin et al [41]. Accordingly, Boyan et al [5] showed that the chemotaxis and mitogenesis responses of human PDL fibroblast are strongest to the BB homodimer of PDGF that binds both of these receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDL cells were grown in 150-cm2 flasks in 25 mL of normal-glucose DMEM supplemented with 10°FBS. When the cells reached subconfluence, the medium was changed to Minimum Essential Medium (MEM, pH 7.4; GIBCO) supplemented with 50 mg/L of ascorbic acid, and the cells were incubated for 48 hr so that cell cycles would be synchronized (Boyan et al, 1994). At various time points (up to 48 hr) after serum re-stimulation (with normal-glucose DMEM containing 10% FBS), the cells were trypsinized and harvested, followed by digestion of cellular protein and RNA.…”
Section: Culture Conditionsmentioning
confidence: 99%